Strategi Pengembangan Usaha Ekonomi Kreatif dalam Meningkatkan Pendapatan Industri Kuliner di Kota Denpasar - I Putu Yoga Arya Semarandana; Made Dwi Setyadhi Mustika (Universitas Veteran Bangun Nusantara, 2025)
The culinary industry in Denpasar City, as part of the creative economy, holds significant potential to boost income in line with the growth of tourism and MSMEs. However, challenges such as intense competition and shifting consumer preferences require businesses to adopt adaptive strategies. This study examines the influence of five factors pricing, business innovation, human resource development, partnerships, and promotion on the income of the culinary sector, while also analysing the moderating role of promotion in the relationship between business innovation and income. A mixed-method approach was employed, combining qualitative and quantitative descriptive methods with a Moderated Regression Analysis (MRA) design. Data were gathered from 122 culinary MSMEs through questionnaires, interviews, and observations. The findings indicate that, collectively, the five variables have a significant impact on income; however, only business innovation and promotion show a significant individual effect. Moreover, promotion strengthens the positive relationship between innovation and income. Entrepreneurs are encouraged to focus on innovating products rooted in local culinary heritage and to utilise digital promotion to expand their market. Government support is expected in the form of training, funding, and culinary tourism promotion. Future research is recommended to explore the influence of digital technology and evolving consumer behaviour within the culinary industry.